P089 THE IMPACT OF VENTRAL HERNIA REPAIR ON PATIENT-REPORTED QUALITY OF LIFE: IDENTIFYING FACTORS ASSOCIATED WITH IMPROVEMENT. (25th November 2021) - Morris, Martin; Patel, Viren; Christopher, Adrienne; Broach, Robyn; Fischer, John
Abstract: Aim: Assessing pre- and postoperative quality of life (QoL) is essential to quantify the magnitude of improvement in disease burden after ventral hernia repair (VHR). Here, we identify patient and operative factors associated with QoL improvement after VHR. Material and Methods: Patients that underwent VHR by a single surgeon were retrospectively identified and included if they had minimum 1 year of follow-up, and completed pre- and postoperative Abdominal Hernia-Q (AHQ) questionnaires. Patients were divided into quintiles based on absolute pre- to postoperative improvement in AHQ score. Chi-squared and fisher's exact tests were used for categorical data, and Student's t-test for continuous data, as appropriate. Results: Compared to the lowest quintile (n = 27, follow-up 32.6 months, mean improvement 3.24 [SD 10.4]), patients in the highest quintile (n = 26, follow up 23.9 months, mean improvement 66.3 [SD 12.1]) were female (76.9% vs 37.0%, p = 0.005 ) with a greater number of previous hernia repairs (mean 2.12 vs. 0.78, p < 0.005 ) and previous abdominal surgeries (mean 4.0 vs 2.0, p < 0.001 ). Patients with greater improvement also had higher incidences of delayed healing (42.3% vs 7.41%), required more office visits (5.54 vs 3.89), and had higher inpatient costs (30, 084 USD vs. 16, 886, all p < 0.05 ). No significant differences were seen in terms of race, ethnicity, body mass index, age, length of stay, Clavien-Dindo scores, hernia recurrence, or other postoperative complications. Conclusions: Despite increased preoperative risk and healthcare burden, some of the most significant QoL improvement after VHR is demonstrated in patients with complex repairs and recoveries. This indicates the global utility of VHR regardless of patient demographics and complicating perioperative factors.